Retention in engineering pathways: an ecological belonging intervention supports help-seeking and continued enrollment - Matthew Bahnson; Allison Godwin; Christian Schunn; Eric McChesney; Linda DeAngelo (International Journal of STEM Education)
Abstract Background The demand for engineers in the workforce continues to rise, which requires increased retention and degree completion at the undergraduate level. Engineering educators need to better understand opportunities to retain students in engineering majors. A strong sense of belonging in engineering represents one important contributor to persistence. However, research has not investigated how academic help-seeking behaviors relate to belonging and downstream outcomes, such as persistence in engineering. Interventions to support and develop belonging show promise in increasing student retention, with particularly positive influences on women, Black, Latino/a/x, and indigenous students. As part of a larger research project, a quasi-experimental intervention to develop a classroom ecology of belonging was conducted at a large Midwestern university in a required first-year, second-semester engineering programming course. The 45-min intervention presented students with stories from past students and peers to normalize academic challenges within the ecology of the classroom as typical and surmountable with perseverance, time, and effort. Results With treatment (n = 737) and control (n = 689) participant responses, we investigated how the intervention condition affected students' comfort with seeking academic help and feeling safe being wrong in class as influences on belonging. Using path analysis, a form of structural equation modeling, we measured the influence of these attitudinal variables on belonging and the influence of belonging beyond a student’s grade point average on enrollment as an engineering major the following fall. The path analysis supports the importance of academic help-seeking and feeling safe to be wrong for belonging, as well as the importance of belonging on continued enrollment. A group path analysis compared the treatment and control groups and demonstrated the positive impact of the intervention on enrollment for the treatment participants. Conclusions The analyses demonstrate the importance of academic help-seeking in students’ sense of belonging in the classroom with implications for identifying effective tools to improve students’ sense of belonging through supporting help-seeking behaviors.